2012
DOI: 10.5951/jresematheduc.43.2.0159
|View full text |Cite
|
Sign up to set email alerts
|

Effects of a Teacher Professional Development Program on the Mathematics Achievement of Middle School Students

Abstract: The effect of a 15- to 24-month in-service professional development (PD) program on state accountability mathematics test scores for middle school students was examined using a quasi-experimental design. Middle level mathematics teachers (n = 128) from 7 school districts and 64 middle schools volunteered for a PD sequence of content-oriented summer courses and pedagogy-oriented structured follow-up experiences during the subsequent academic year. Student effects of the PD program were measured using Colorado's… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
15
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 40 publications
(16 citation statements)
references
References 21 publications
1
15
0
Order By: Relevance
“…Research has provided emerging evidence that certain characteristics of PD are important for influencing changes in classroom practice and supporting student achievement (Heck et al 2008, Sample McMeeking et al 2012. For example, programs with a focus on subject matter knowledge and student learning in that subject are more likely to have an impact on student achievement than those focused on more generic topics (Kennedy 1999, Cohen andHill 2000).…”
Section: Similarity and The Common Core State Standardsmentioning
confidence: 99%
“…Research has provided emerging evidence that certain characteristics of PD are important for influencing changes in classroom practice and supporting student achievement (Heck et al 2008, Sample McMeeking et al 2012. For example, programs with a focus on subject matter knowledge and student learning in that subject are more likely to have an impact on student achievement than those focused on more generic topics (Kennedy 1999, Cohen andHill 2000).…”
Section: Similarity and The Common Core State Standardsmentioning
confidence: 99%
“…Professionalism is imperative for teachers because it affects teaching quality (see Gore, Lloyd, Smith, Bowe, Ellis, & Lubans, 2017) and student achievement (see Sampel McMeeking, Orsi, & Cobb, 2012).…”
Section: Introductionmentioning
confidence: 99%
“…Table 5.1 displays these results. Greenwald, Hedges, and Laine (1996) and Sander (1999) in that class size reduction matters, but also adds value to the professional development findings by Blank (2013), Iatorola and Fruchter (2004), Heller et al, (2011), andSample McMeeking, Orsi, andCobb (2012) in that professional development can have an impact on achievement. From a larger perspective, this finding also supported the notion that resources in the classroom can be allocated in such a way to improve district effectiveness.…”
Section: Additional Findingssupporting
confidence: 52%
“…The professional development program was designed to give teachers deeper content knowledge and to use an-inquiry based approach to math. Again the authors found that students with teachers who participated in these programs performed significantly better on standardized tests than teachers who did not (Sample McMeeking, Orsi, and Cobb, 2012).…”
Section: Professional Developmentmentioning
confidence: 97%
See 1 more Smart Citation